2012
DOI: 10.1371/journal.ppat.1002756
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Group B Antigen of Streptococcus agalactiae: A Peptidoglycan-Anchored Polysaccharide Involved in Cell Wall Biogenesis

Abstract: Streptococcus agalactiae (Group B streptococcus, GBS) is a leading cause of infections in neonates and an emerging pathogen in adults. The Lancefield Group B carbohydrate (GBC) is a peptidoglycan-anchored antigen that defines this species as a Group B Streptococcus. Despite earlier immunological and biochemical characterizations, the function of this abundant glycopolymer has never been addressed experimentally. Here, we inactivated the gene gbcO encoding a putative UDP-N-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 53 publications
4
85
0
Order By: Relevance
“…As previously reported (28)(29)(30), the depletion of proteins involved in the cell division/separation process in both Gram-positive and Gram-negative bacteria produces a phenotype very similar to that observed with the spyAD knockout strain.…”
Section: Resultssupporting
confidence: 79%
“…As previously reported (28)(29)(30), the depletion of proteins involved in the cell division/separation process in both Gram-positive and Gram-negative bacteria produces a phenotype very similar to that observed with the spyAD knockout strain.…”
Section: Resultssupporting
confidence: 79%
“…This step is poorly characterized and the molecular principles for capsule attachment in Gram-positive bacteria have rarely been addressed. For example, NMR analysis of mutanolysin cleaved sacculi revealed that CPS type III of GBS is linked via a glycosidic linker to N-acetylglucosamine residues of peptidoglycan (6), whereas the Lancefield group B carbohydrate of GBS appears to be linked to N-acetylmuramic residues of peptidoglycan with an intervening linkage unit (6,58). In Bacillus anthracis, the capsule is composed of a poly-D-␥-glutamate polymer, and is also attached to peptidoglycan.…”
Section: Discussionmentioning
confidence: 99%
“…7). Considering the involvement of LCP proteins in transferring polymers for which synthesis is initiated by TagO (31,37,50,51,58,59,66,67), we examined whether capsule assembly requires tagO in S. aureus. Furthermore, recent work has shown that heterologous expression of Pseudomonas aeruginosa O11 lipopolysaccharide synthesis genes, which include wbpL, a UDP-FucNAc-1-phosphate transferase, together with CP5 genes capHIJK was sufficient to synthesize lipid-linked CP5 polymer repeats in E. coli (68).…”
Section: Discussionmentioning
confidence: 99%
“…Teichoic or teichuronic acids are typical and well‐studied SCWP in Gram‐positive bacteria and play an important role in normal cell function and infection (Weidenmaier and Peschel, 2008). Many β‐hemolytic streptococcal species appear to lack expression of typical teichoic or teichuronic acid structures (Sutcliffe et al ., 2008; Caliot et al ., 2012) and instead express a rhamnose‐rich polymer, which comprises approximately half of the cell wall mass (McCarty, 1952). Historically, expression of these evolutionary conserved glycans underlies classification of β‐hemolytic streptococci in Lancefield groups (A, B, C, G …) (Lancefield, 1933), a feature that is still applied in contemporary rapid test kits to diagnose streptococcal infections.…”
Section: Introductionmentioning
confidence: 99%